Mortgage as a legal instrument for enforcement of the contract of sale - Gojani, Skender (Technium Social Sciences Journal, 2021)
Mortgage is a real means of securing the contract, the contracting parties, in many cases agree to finalize their agreement on a certain item by concluding a written contact, but in some cases the contracting parties can also be ensured in various ways to adhere to the rights and obligations arising from their contract. The creditor on the one hand as the pledgee and the debtor on the other hand as the pledgor are those who enter into a contract by which they create their rights and obligations arising from the contract which must be drafted in support of the provisions of the Law on Obligational Relationships. At the time of entering into the contract they can also enter into a mortgage contract as a real means of securing the contract, where the creditor is assured that if the debtor does not meet the main contractual requirement, then by mortgage as a real means of securing the contract he will realize the main requirement of the contract, i.e. through the mortgage as a real means of securing the contract the pledgee creditor manages to fulfill the main requirement of the contract which the debtor has not been able to meet by the pledgor.